Metode Pembelajaran English Fun Dengan Short Movie Di SDN 004 Sepaku - Zulfikar, Iwan; Pebriyana, Aurelia (Jurnal Pengabdian UntukMu NegeRI, 2024)
The English Fun learning method is one of the methods for teaching English. English is one of the most widely used languages in the world across various fields. The lack of interest among children in learning English is very concerning. The implementation team aims to introduce an enjoyable and engaging English learning method, especially for elementary school children. The program conducted is called English Fun, utilizing short movies as its medium. This program aims to increase children's interest in learning English through the English Fun method. The activity was carried out on February 15, 2024, at SDN 004 Sepaku, Desa Bukit Raya. This activity was targeted at 36 third-grade students. The results of the community service activity conducted at SDN 004 Sepaku provided significant and necessary benefits to the students at the school, namely an increase in their interest in learning English.